Tracer and Employability Study: BS Tourism Graduates of Laguna State Polytechnic University Los Banos Campus - Buama, C A C (KnE Social Sciences, 2018)
The main thrust of the study was to assess and trace the employability of graduates of Bachelor of Science in Tourism from LSPU LB Campus AY 2009-2013. The instrument used was an adopted and modified tracer questionnaire that was then validated by pool of experts in the field. The respondents of the study were the BS Tourism graduates class of 2009 to 2013. Total enumeration was employed as sampling technique. The frequency and the percent distributions were used in presenting the profile of the respondents on the employability of graduates of Bachelor of Science in Tourism. Based from the findings of the study it revealed the relevant reasons behind their difficulty in landing a job were lack of work experience; no personal connections/strong referrals; there are very few jobs hence there is a strong competition and; economic recession; For the employed graduates, 57 or 100% said that it took them 6 months before landing their first job after graduating from college. Out of 57 employed respondents, 55 or 96% are working in the government sector. It indicates that majority of the graduates still prefer to render their services to our Motherland. Moreover, 38 or 67% of the respondents’ company are engaged in service; For the present position, 47 or 82% are in a rank-and file level. Moreover, the empirical findings of this research led to the following conclusions that there is a need to improve the employment rate of BS Tourism at the LSPU-LB Campus; The graduates are challenged by the lack of opportunity and by their lack of competence. The findings of the study yield the following recommendations: Functional facilities must be sustained; continual job placement services should be strengthened; The university administration may consider additional faculty members in the field of tourism management. Keywords: Employability, Tourism, Graduates